PENGARUH BEBERAPA FAKTOR TERHADAP KINERJA KEUANGAN DENGAN CORPORATE SOCIAL RESPONSIBILITY SEBAGAI VARIABEL INTERVENING : (Studi Kasus Pada Perusahaan Manufaktur Sub Sektor Industri Konsumsi Yang Terdaftar Di Bursa Efek Indonesia) - Rahmi Nur Islami; Nizhamuddin AB (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2023)
The Influence of Several Factors on Financial Performance with Corporate Social Responsibility as an Intervening Variable (Case Study in Manufacturing Companies in the Consumer Industry Sub Sector Listed on the Indonesia Stock Exchange. This research was conducted with the aim of examining and analyzing the effect of environmental performance, environmental costs and company size on financial performance mediated by Corporate Social Responsibility. The population in this study are manufacturing companies in the Consumer Industry Sub Sector which are listed on the Indonesia Stock Exchange (IDX) during the period 2017 to 2021. The sample selection technique used purposive sampling so that 5 companies were obtained with a total of 24 data. The results of these data have been tested by classical assumptions in the form assumption of normality, assumption of multicollinearity, assumption of heteroscedasticity, and assumption of autocorrelation. Methods of data analysis using multiple linear regression techniques. The results of the study simultaneously show that Environmental Performance, Environmental Costs and Company Size have a positive effect on Corporate Social Responsibility, Corporate Social Responsibility has a significant positive effect on Financial Performance and Environmental Performance, Environmental Costs, and Company Size have a positive effect on Financial Performance mediated by Corporate Social Responsibility.